Orofacial characteristics and dental management in a child with moyamoya disease. Issue 5 (21st May 2021) - Rahul, Morankar; Sultan, Farheen; Tewari, Nitesh; Mathur, Vijay
Abstract : Moyamoya disease is a chronic, progressive intracranial arteriopathy. It is characterised by progressive stenosis/occlusion of distal intracranial carotid and cerebral arteries. It is associated with a high risk of ischaemic and haemorrhagic stroke. Hereditary, infectious and inflammatory factors have been found to be associated with this condition; however, its aetiology is still unclear. The estimation of disease prevalence is approximately 1.6 to 16.1 in 100 000 live births. This article presents the case of a 5-year-old girl child diagnosed with moyamoya disease, placing emphasis on the clinical and radiographic orofacial characteristics of the case and its dental management.